Improving Performance of Fly Ash Pump in Coal Boilers - Jiao J.J.; Deni Nugraha; Dede Rustamli; Muslimin Muslimin; Andi Rinaldi Hasan (Nusa Putra University, 2019)
Fly ash is a system of dry ash handling system burning coal by b oiler before getting to the chimney so as not to pollute the environment (air). Abu will pass the E lecture Static Recipient ( ESP ) and be temporarily accommodated at hopper . Then the ash will be transferred through the pneumatic AV pump system to fly ash silo . Fly ash transfer system failure occurred due to disruption of the pneumatic control system pump pa da AV system. This is because of the dome valve insert seal on AV pump leak and control system pneumatic fault because of contaminated by fly ash dust . The working intensity of the AV pump system in operation creates friction between the dome valve and dome valve insert seal which can cause erosion and leak on the dome valve insert seal . Frequent leakage at dome valve insert seal , has an impact on the spare part control system pneumatic contaminated by fly ash dust which causes damage to pneumatic spare parts and the cessation of the transfer process of ash to fly ash silos.The research was conducted with the addition of protection to the system pneumatic control AV pump by installing a quick exhaust valve on the system pneumatic AV pump in fly ash system , so that dust does not enter the AV pump's pneumatic control system when a dome valve insert seal leaks .